Edukasi Literasi Keuangan Pelajar Indonesia di Malaysia melalui Pengenalan Mata Uang dan Menabung - Pratiwi, Erina; Hidayati, Nur; Kusumaningarti, Miladiah (Jurnal SOLMA, 2026)
Background: This community service activity aimed to increase the financial literacy of Indonesian students in Kampung Melayu, Sungai Buloh, Malaysia, through currency introduction and savings education based on visual learning and direct practice. The program was implemented as part of the International Community Service Program (KKN) of Universitas Islam Kadiri from 3–30 August 2025, with two main sessions conducted on 12 and 14 August 2025. The activity involved 27 participants aged 5–14 years at the Kampung Melayu Sungai Buloh Guidance Center. Methods: The activities were carried out in three stages: preparation, implementation, and evaluation. An experiential and participatory learning approach was applied, using visual learning media and hands-on practice to make piggy banks from recycled materials. Results: Activity documentation showed an improvement in participants’ understanding of the differences between Rupiah and Ringgit currencies, as well as an increased interest in independent saving. The activity also received positive responses from the guidance center management, with participants demonstrating active involvement and high enthusiasm throughout the learning process. Conclusion: This activity is effective in introducing basic financial literacy concepts through experiential learning and direct practice. However, differences in participants’ age levels remain a challenge; therefore, continuous implementation with age-appropriate material development is recommended to enhance long-term learning outcomes.